An Agreement between the University of Manchester and BRAC University for the project "Community and institutional responses to the challenges facing poor urban people in an era of global warming in Bangladesh" (2011) - BRAC University; University of Manchester (BRAC University and University of Manchester, 2013)
1. Terms of reference and services to be supplied. 2. Conditions. 3. Duration. 4. Intellectual property ownership. 5. Confidentiality. 6. Payment. 7. Indemnity. 8. Termination. 9. Assignment and subcontracting. 10. Amendments. 11. Contradiction. 12. Rights of thirds. 13. Law.